CO2‐Assisted Fabrication of Two‐Dimensional Amorphous Molybdenum Oxide Nanosheets for Enhanced Plasmon Resonances. Issue 6 (3rd January 2017) - Liu, Wei; Xu, Qun; Cui, Weili; Zhu, Chuanhui; Qi, Yuhang
Abstract: As a remarkable class of plasmonic materials, two dimensional (2D) semiconductor compounds have attracted attention owing to their controlled manipulation of plasmon resonances in the visible light spectrum, which outperforms conventional noble metals. However, tuning of plasmonic resonances for 2D semiconductors remains challenging. Herein, we design a novel method to obtain amorphous molybdenum oxide (MoO3 ) nanosheets, in which it combines the oxidation of MoS2 and subsequent supercritical CO2 ‐treatment, which is a crucial step for the achievement of amorphous structure of MoO3 . Upon illumination, hydrogen‐doped MoO3 exhibits tuned surface plasmon resonances in the visible and near‐IR regions. Moreover, a unique behavior of the amorphous MoO3 nanosheets has been found in an optical biosensing system; there is an optimum plasmon resonance after incubation with different BSA concentrations, suggesting a tunable plasmonic device in the near future. Abstract : Better off amorphous : Amorphous MoO3 nanosheets were fabricated through the oxidation of MoS2 and subsequent treatment with supercritical CO2 . Hydrogen‐doped MoO3 formed via a facile solar‐light‐driven process exhibits surface plasmon resonances (SPR) in the visible and NIR regions. In an optical biosensing system the SPR correlates with bovine serum albumin concentrations.